1994
DOI: 10.1007/bf02382726
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent exaggeration in female catarrhine primates

Abstract: ABSTRACT. Adolescent females of 11 primate species display exaggerated versions of the cues to sexual cycle state or fertility which are displayed by adult females: anubis baboons; geladas; Assamese, Barbary, crab-eating, Japanese, and stump-tailed macaques; patas monkeys; gorillas; and humans. These cases are briefly described and a variety of hypotheses is presented and evaluated to account for the adolescent exaggeration. Such exaggeration may be a super-normal sexual stimulus, a barrier to cross-species hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 68 publications
3
32
1
Order By: Relevance
“…Sexual swellings in simakobu (Simias concolor) have also been reported [Tenaza, 1989]. Similarly to the current findings in the proboscis monkey, exaggerated swelling in adolescent female primates has been reported in 11 species [reviewed in Anderson & Bielert, 1994], and is also distinct in adolescent simakobu monkeys [Tenaza, 1989]. Nasalis and Simias are considered to be closely related species [Groves, 1989] and may preserve common features.…”
Section: Discussionsupporting
confidence: 54%
“…Sexual swellings in simakobu (Simias concolor) have also been reported [Tenaza, 1989]. Similarly to the current findings in the proboscis monkey, exaggerated swelling in adolescent female primates has been reported in 11 species [reviewed in Anderson & Bielert, 1994], and is also distinct in adolescent simakobu monkeys [Tenaza, 1989]. Nasalis and Simias are considered to be closely related species [Groves, 1989] and may preserve common features.…”
Section: Discussionsupporting
confidence: 54%
“…It has been reported that adolescent females of both Japanese and rhesus macaques exhibit sexual swellings [Anderson and Bielert, 1994]. However, no Japanese macaques aged 4-6 years exhibited sexual swelling, while 11 of the 13 rhesus macaques aged 3-5 years did in this study.…”
Section: Discussioncontrasting
confidence: 45%
“…These two macaques share similar reproductive features [reviewed in Thierry, 2010] like, for example, ovarian cycle length (Japanese macaques: 26.5 days; rhesus macaques: 28.3 days), a multimale-multifemale social structure, multimounting behaviour and seasonal breeding, but the age at first birth is later in Japanese macaques (Japanese macaques: 5 years; rhesus macaques: 4 years). Sexual swelling is recognized in adolescent females of both species [Anderson and Bielert, 1994], and females' red sexual skin draws male attention [Waitt et al, 2006;Wallner et al, 2011]. However, the sexual skin of Japanese macaques swells less obviously and is much redder than that of rhesus macaques [observed by J.S.].…”
mentioning
confidence: 99%
“…First, pulses of gonadotropin releasing hormone (GnRH) from the hypothalamus increase in frequency and amplitude, stimulating anterior pituitary gonadotropin secretion, ovarian follicular development, and gonadal steroid secretion (Terasawa & Fernandez, 2001). Increases in neuroendocrine activity stimulate marked perineal sexual swellings in adolescent female rhesus monkeys, swellings which are not present in adult females and which decrease with successive breeding seasons (Anderson & Bielert, 1994;Hisaw & Hisaw, 1961). Although increased steroid secretion stimulates uterine endometrial development and eventually menstruation (Salamonsen, Kovacs, & Findlay, 1999), early menstrual cycles are typically not associated with ovulation and rarely result in conception.…”
Section: Pubertal Changes In Physiology and Behaviormentioning
confidence: 99%